Weight as an assay-independent predictor of poor response to enteric aspirin in cardiovascular patients. (18th May 2020) - McCall, Meadhbh; Peace, Aaron; Tedesco, Anthony F; Foley, David; Conroy, Ronán M; Cox, Dermot
Abstract: Aspirin non-response is associated with poor outcome but there is no agreement between the different methods to asses it. Weight has been shown to be a predictor of poor response but only using one method. In this study, we determine the effects of weight on different assays of platelet function. The response to aspirin was determined in 138 cardiology patients using serum thromboxane, arachidonic acid-induced platelet aggregation and VerifyNow©. Twenty-five percent of patients showed an inadequate response to aspirin in at least one assay on the initial test. After ensuring patient compliance only 5% of patients were considered to be non-responders. Only 9% of non-responders were non-responsive in all three assays. When switched to plain aspirin, only 2% of patients were non-responsive. All patients responded adequately to 150 mg aspirin. The non-responders were significantly heavier than responders (78.5 kg ± 14.0 (SD); BMI: 28.4 kg/m 2 ± 4.4 v's 102.6 kg ± 20.6, P = .0016; BMI: 38.3 kg/m 2 ± 7.6, P = .0015). A rule-based approach of using plain aspirin in patients over 90 kg or BMI 32 along with patient education to ensure compliance will ensure that all patients respond to their aspirin without the need for testing.